Studi Kitab Syarh Shahih al-Bukhari karya Ibnu Bathal - Syamsudin, Kinkin (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Shahih al-Bukhari is a phenomenal book among the many books of matan hadith that have been written, and one form of attention of scholars towards it is to make the book of Sharah. The books of sharah are written by scholars from various madhhabs, one of which was written by Ibn Bathal who is affiliated with the Maliki madzhab. Using the method of library research and through the content analysis approach, this article was written to find out the methodology of writing Sharah Shahih al-Bukhari by Ibn Bathal and reveal the difference with other books of Sharah Shahih al-Bukhari. From this research it can be known that the peculiarities of Ibn Bathal's work are; First, he did not discuss rawi and sanad specifically, but immediately mentioned the name of the friend who became the hadith narration. Second, he explained the matan hadith without discussing ikhtilaf or the difference in matan editor first. Third, in the difference in understanding the disputed matan, especially with regard to the law, it takes more interpretations from the Maliki madzhab.